2017
DOI: 10.1038/nrn.2017.111
|View full text |Cite
|
Sign up to set email alerts
|

Managing competing goals — a key role for the frontopolar cortex

Abstract: Humans are set apart from other animals by many elements of advanced cognition and behaviour, including language, judgement and reasoning. What is special about the human brain that gives rise to these abilities? Could the foremost part of the prefrontal cortex (the frontopolar cortex), which has become considerably enlarged in humans during evolution compared with other animals, be important in this regard, especially as, in primates, it contains a unique cytoarchitectural field, area 10? The first studies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
201
4
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(217 citation statements)
references
References 100 publications
10
201
4
2
Order By: Relevance
“…Both exploration types might thus depend on similar structures tracking uncertainty. Mansouri et al (2017) recently proposed a functional model of the human FPC in which distinct subregions of the FPC play different functional roles in exploration. In this model, lateral FPC is involved in uncertainty-based exploration, which entails an online tracking of relevant choice alternatives in order to potentially re-engage one of these alternatives as replacement for the currently exploited strategy.…”
Section: Neural Correlates Of Exploration and Exploitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Both exploration types might thus depend on similar structures tracking uncertainty. Mansouri et al (2017) recently proposed a functional model of the human FPC in which distinct subregions of the FPC play different functional roles in exploration. In this model, lateral FPC is involved in uncertainty-based exploration, which entails an online tracking of relevant choice alternatives in order to potentially re-engage one of these alternatives as replacement for the currently exploited strategy.…”
Section: Neural Correlates Of Exploration and Exploitationmentioning
confidence: 99%
“…These findings regarding the roles of striatal and frontal DA in exploration resonate with cognitive neuroscience studies suggesting that exploration and exploitation rely on distinct neural systems. Daw et al (2006) showed that frontopolar cortex (FPC) is activated during exploratory choices, possibly facilitating behavioral switching between an exploitative and exploratory mode by overriding value-driven choice tendencies (Daw et al, 2006;Badre et al, 2012;Addicott et al, 2014;Mansouri et al, 2017). In line with this idea, up-and down-regulation of FPC excitability via transcranial direct current stimulation (TDCS) increases and decreases exploration during reward-based learning (Becharelle et al, 2015).…”
Section: Introductionmentioning
confidence: 98%
“…An inability of the vmPFC to differentially respond to threat versus safety, and corresponding autonomic inflexibility reflected in reduced PRV, may contribute to elevated threat responding in an objectively safe context. The region of vmPFC identified here corresponds to frontopolar cortex or medial BA10, a region that has expanded considerably in humans relative to nonhuman primates and which is theorized to be important for shifting attentional or executive resources away from current goals to other potential goals in the environment (Mansouri, Koechlin, Rosa, & Buckley, ). This perspective on the broad function of BA10 is not inconsistent with the flexible, context‐specific, inhibitory control function ascribed by Thayer and colleagues () to HRV.…”
Section: Discussionmentioning
confidence: 99%
“…18 In major depression, levels of transmembrane TNF, but not soluble TNF, were 458% higher in the dorsolateral prefrontal cortex, but not the anterior cingulate cortex. 19 In interpreting the significance of changes in TNFrelated pathways in the cortex of mood disorders, it is significant that the frontopolar prefrontal cortex is thought to be involved in the coordination of highlevel cognitive processes and emotional control, 39,40 the anterior cingulate cortex is involved in emotional regulation and processing 41 and the dorsolateral prefrontal cortex is associated with cognition, executive function and regulation of negative emotions. 42 Notably, the frontopolar prefrontal cortex, [43][44][45] anterior cingulate cortex 41,46,47 and dorsolateral prefrontal cortex [46][47][48] have all been reported to be dysfunctional in patients with mood disorders.…”
Section: Tnf Abnormalities In Mood Disordersmentioning
confidence: 99%